Downregulation of Cullin 3 Ligase Signaling Pathways Contributes to Hypertension in Preeclampsia - Zhang, Ya; Jiang, Gengru; Zhang, Chong (Frontiers in Cardiovascular Medicine, 2021)
Background: Preeclampsia (PE) is a leading cause of maternal and perinatal morbidity and mortality; however, the etiology and pathophysiology of it remain obscure. PE is initiated by inadequate spiral artery remodeling and subsequent placental ischemia/hypoxia, which stimulates release of bioactive factors into maternal circulation, leading to hypertension and renal damage. Methods and Results: Abundance of key components of Cullin 3 RING Ubiquitin Ligase (CRL3), including Cullin 3 (CUL3) and its neddylated modification, and adaptors including Kelch-like 2 (KLHL2) and Rho-related BTB domain containing protein 1 were all decreased in spiral arteries and placentas of PE patients. Similar changes were found in aortic tissues and renal distal tubules of pregnant mice treated with Nω-nitro-l-arginine methyl ester hydrochloride. The downregulation of CRL3 function led to accumulation of with-no-lysine kinases, phosphodiesterase 5 and RhoA in vessels and renal distal tubules, which promoted vasoconstriction and Na-Cl cotransporter activation in the distal convoluted tubule (DCT), as well as vascular and DCT structure remodeling. Proton pump inhibitor Esomeprazole partially restored CRL3 function. In vitro studies have showed that increased abundance of JAB1, a component of the COP9 signalosome, inhibited CUL3 neddylation and promoted the expression of hypoxia-inducible factor 1α, which down-regulated peroxisome proliferator-activated receptor γ and further promoted CUL3 inactivation. KLHL3/2 was degraded by increased autophagy. Conclusion: These findings support that the downregulation of CRL3 function disrupts the balance of vasoconstriction and vasodilation and aggravates excess reabsorption of sodium in PE.